2016
DOI: 10.1037/pspi0000066
|View full text |Cite
|
Sign up to set email alerts
|

The expression and recognition of emotions in the voice across five nations: A lens model analysis based on acoustic features.

Abstract: This study extends previous work on emotion communication across cultures with a large-scale investigation of the physical expression cues in vocal tone. In doing so, it provides the first direct test of a key proposition of dialect theory, namely that greater accuracy of detecting emotions from one's own cultural group-known as in-group advantage-results from a match between culturally specific schemas in emotional expression style and culturally specific schemas in emotion recognition. Study 1 used stimuli f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 91 publications
6
88
1
1
Order By: Relevance
“…However, it is only in recent years that empirical work has started to address the question of whether different positive emotions are associated with discrete vocal signatures. Increasingly, emotion researchers are starting to go beyond a single positive emotion and instead include vocal expressions of multiple positive emotions including achievement, amusement, contentment, pleasure, and relief (e.g., Anikin & Persson, 2016;Laukka et al, 2016;Lima, Castro, & Scott, 2013;Sauter & Scott, 2007).…”
Section: Discrete Positive Emotions In the Human Voicementioning
confidence: 99%
“…However, it is only in recent years that empirical work has started to address the question of whether different positive emotions are associated with discrete vocal signatures. Increasingly, emotion researchers are starting to go beyond a single positive emotion and instead include vocal expressions of multiple positive emotions including achievement, amusement, contentment, pleasure, and relief (e.g., Anikin & Persson, 2016;Laukka et al, 2016;Lima, Castro, & Scott, 2013;Sauter & Scott, 2007).…”
Section: Discrete Positive Emotions In the Human Voicementioning
confidence: 99%
“…Research has shown that despite some cultural diversity, there is a basic universal understanding of the emotional cues presented in speech [24]. While the participants in the control group of this study could not understand the French lyrics, they may have been able to pick up on the mood of the song, which keeps in line with typical contemporary rap.…”
Section: Discussionmentioning
confidence: 70%
“…48 Ge et al, 2009;Tanaka et al, 2013;Wang et al, 2015) found that face recognition differs between the ingroup and outgroup as well as evidence for different processing of face stimuli between the respective groups (Laukka et al, 2016;Tanaka et al, 2004;Young et al, 2012). Thus, our finding can be taken as evidence that it is important to distinguish between interpersonal impression formation and face recognition processes.…”
Section: Prejudice At First Sight?mentioning
confidence: 99%